Acoustic radiation force impulse imaging for assessing graft fibrosis after pediatric living donor liver transplantation: A pilot study. Issue 11 (21st September 2013) - Tomita, Hirofumi; Hoshino, Ken; Fuchimoto, Yasushi; Ebinuma, Hirotoshi; Ohkuma, Kiyoshi; Tanami, Yutaka; Du, Wenlin; Masugi, Yohei; Shimojima, Naoki; Fujino, Akihiro; Kano, Motohiro; Fujimura, Takumi; et al.
<x xml:space="preserve">Abstract</x> Graft fibrosis is a common finding during protocol biopsy examinations after pediatric liver transplantation. We evaluated the clinical utility of liver stiffness measurements by acoustic radiation force impulse (ARFI) imaging, a novel ultrasound‐based elastography method, for assessing graft fibrosis after pediatric living donor liver transplantation (LDLT). We performed 73 liver stiffness measurements by ARFI imaging in 65 pediatric LDLT recipients through the upper midline of the abdomen (midline value) and the right intercostal space (intercostal value) around the time of protocol biopsy examinations. Fifty‐nine of these liver stiffness measurements could be compared with histopathological findings. Graft fibrosis was assessed according to the degrees of portal and pericellular fibrosis. Significant fibrosis, which was defined as F2 or worse portal fibrosis and/or moderate or worse pericellular fibrosis, was observed in 14 examinations, which had significantly higher midline (P = 0.005) and intercostal values (P < 0.001) than the others. Liver stiffness measurements by ARFI imaging significantly increased with increases in the portal and pericellular fibrosis grades. For the diagnosis of significant fibrosis, the areas under the receiver operating characteristic curve (AUROCs) were 0.760 (P = 0.005) and 0.849 (P < 0.001) for the midline and intercostal values, respectively. The optimal cutoff values were 1.30 and 1.39 m/second for midline and intercostal values, respectively. Slight but significant elevations were noted in the results of biochemical liver tests: serum levels of γ‐glutamyltransferase showed the highest AUROC (0.809, P = 0.001) with an optimal cutoff value of 20 IU/L. In conclusion, liver stiffness measurements by ARFI imaging had good accuracy for diagnosing graft fibrosis after pediatric LDLT. The pericellular pattern of fibrosis was frequently observed after pediatric LDLT, and moderate pericellular fibrosis was detectable by ARFI imaging. Liver Transpl 19:1202–1213, 2013. © 2013 AASLD.